DEVELOPMENT OF THE BRIKUDA BUSINESS MODEL AS AN ALTERNATIVE ENERGY SOURCE TO ENHANCE ECONOMIC VALUE USING THE BUSINESS MODEL CANVAS APPROACH - Rio Firmansyah; M.Oktaviannur (PT. Jurnal Center Indonesia Publisher, 2026)
The global demand for energy continues to increase alongside population growth and rapid industrial development, while dependence on fossil fuels remains high. This presents challenges related to environmental degradation, carbon emissions, and concerns over long-term energy availability. Biomass-based alternative energy has emerged as one of the strategic solutions to support sustainable energy transitions, particularly in developing countries such as Indonesia. One potential biomass source that remains underutilized is horse manure, which can be processed into briquettes known as Brikuda. This study aims to analyze the potential of Brikuda as an alternative energy source and to develop a sustainable business model using the Business Model Canvas (BMC). A qualitative descriptive approach was employed, involving in-depth interviews, direct observations, and analysis of secondary data. The findings reveal that Brikuda has strong potential as a renewable fuel due to the abundant availability of horse manure in Bandar Lampung. It offers economic benefits, reduces environmental pollution, and supports local empowerment. The Business Model Canvas analysis shows that farmers and livestock breeders are the primary customer segments, while the value proposition emphasizes affordability, environmental friendliness, and ease of use. The study concludes that the Brikuda business model can enhance local economic value, promote sustainable waste management, and serve as a feasible alternative energy innovation. The research contributes to the development of renewable energy entrepreneurship and provides a reference for policy formulation in promoting local-based bioenergy initiatives.